Composite catalyst, preparation method thereof and method for preparing cyclohexenyl cyclohexanone

By using composite support and metal oxide-supported composite catalysts, the problems of low catalytic activity and unsatisfactory cycle stability of existing catalysts were solved, and efficient and green cyclohexanone dimer preparation was achieved.

CN119680628APending Publication Date: 2025-03-25BEIJING HYWIN HYDROGEN ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411862191.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing catalysts for preparing cyclohexenyl cyclohexanone have low catalytic activity, and it is difficult to take into account the high conversion rate of cyclohexanone and the dimer selectivity of the catalyst, and the multiple cycle stability of the catalyst is not ideal.

Method used

A composite catalyst is provided, including alumina and molecular sieve as composite support, and titanium oxide and/or zirconia as metal oxides. The catalyst forms a composite catalyst with high catalytic activity and cycle stability by a specific preparation method including mixing, forming, first calcining, and second calcining.

Benefits of technology

The composite catalyst exhibits high catalytic activity in the cyclohexanone self-condensation reaction, taking into account high cyclohexanone conversion and dimer selectivity, and has high cyclic stability. It can basically maintain its activity and selectivity during the first use after 5 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193457820000011
    Figure BDA0005193457820000011
  • Figure BDA0005193457820000151
    Figure BDA0005193457820000151
  • Figure BDA0005193457820000161
    Figure BDA0005193457820000161
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a composite catalyst and a preparation method thereof, and a method for preparing cyclohexenyl cyclohexanone. The composite catalyst comprises a composite carrier and a metal oxide loaded on the composite carrier; wherein the composite carrier comprises aluminum oxide and a molecular sieve; wherein the weight ratio of the aluminum oxide to the molecular sieve is 1: (0.1-10); the metal oxide comprises titanium oxide and / or zirconium oxide; the weight ratio of the composite carrier to metal elements in the metal oxide is 100: (1-50). The catalyst has high catalytic activity in the reaction for preparing the dimer through the cyclohexanone self-condensation reaction, the reaction condition is mild, high cyclohexanone conversion rate and high dimer selectivity can be both considered, and high cycle stability is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a composite catalyst and a preparation method thereof, and a method for preparing cyclohexenylcyclohexanone. Background Art

[0002] 2-(1-cyclohexenyl)cyclohexanone and its resonance isomers can be used as special solvents, and can also be used in herbicides, wood preservatives, pesticides, etc. Its large-scale application is as an important intermediate for the two-step synthesis of o-phenylphenol (OPP). O-phenylphenol is an important fine chemical intermediate that can be used to synthesize new flame retardants, surfactants, plastic heat stabilizers, etc. Previously, the production of o-phenylphenol was mainly to recover OPP from the distillation residue of phenol produced by the sulfonation method. The OPP obtained by this method has a low yield and low purity. With the shutdown and transfer of the sulfonation process for producing phenol, this method has been basically eliminated. In view of the market demand for OPP, it is urgent to develop a mature new synthesis process. The most widely used and promising one at present is the cyclohexanone self-condensation dehydrogenation method. The specific process is that the raw material cyclohexanone self-condenses to generate 2-(1-cyclohexenyl)cyclohexanone and its resonance isomers, two dimers (as shown below), and then gas phase dehydrogenation generates OPP.

[0003]

[0004] The traditional synthesis method of cyclohexanone dimer is to use concentrated sulfuric acid, concentrated hydrochloric acid or methanesulfonic acid as a catalyst, and synthesize it by dehydration of two molecules. Liquid acid catalysts have problems such as severe equipment corrosion, alkaline neutralization treatment of waste liquid leading to severe environmental pollution, and many side reactions.

[0005] CN101003471A discloses a method for producing cyclohexenylcyclohexanone by continuous condensation of cyclohexanone. The preparation steps include premixing, preheating, reaction, water washing and alkali washing. During the premixing process, cyclohexanone is mixed with a solid superacid catalyst in a premixing kettle. The solid superacid catalyst is phosphotungstic acid, activated carbon-supported phosphotungstic acid, cationic resin-supported FeCl3 or SiO2-supported FeCl3. The method has a low single-pass conversion rate of only 45-50%, and the production operation is complicated, including mixing, preheating, multi-stage reaction, water washing, alkali washing and other processes.

[0006] CN102557908A discloses a method for preparing 2-(cyclohex-1'-enyl)cyclohexanone. The solid acid catalyst used in the method has the following chemical formula: Al x S y O z, wherein x, y, and z represent atomic ratios, and x is 1 to 4, y is 1 to 3, and z is a value that can satisfy the valence requirements of Al and S in an oxidized state present in the catalyst. This method is difficult to achieve both high cyclohexanone conversion and dimer selectivity at the same time.

[0007] Therefore, developing a solid catalyst with high catalytic activity, high cyclohexanone conversion rate and high dimer selectivity, high cyclic stability, easy separation, and environmental friendliness is of great significance for achieving efficient and green preparation of cyclohexanone dimer. Summary of the invention

[0008] The present invention aims at the problems that the existing catalyst for preparing cyclohexenylcyclohexanone has the problem that the catalytic activity needs to be improved, it is difficult to take into account both a high cyclohexanone conversion rate and a high dimer selectivity, and the catalyst has the problem that the multiple cycle stability is not ideal. A composite catalyst and a preparation method thereof, and a method for preparing cyclohexenylcyclohexanone are provided.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite catalyst, which comprises a composite carrier and a metal oxide supported on the composite carrier; wherein:

[0010] The composite carrier comprises alumina and molecular sieve; wherein the weight ratio of alumina to molecular sieve is 1:(0.1-10);

[0011] The metal oxide includes titanium oxide and / or zirconium oxide;

[0012] The weight ratio of the composite carrier to the metal element in the metal oxide is 100:(1-50).

[0013] A second aspect of the present invention provides a method for preparing a composite catalyst, the method comprising:

[0014] (1) mixing raw materials including an aluminum source, a molecular sieve and a binder, and subjecting the resulting mixture to a molding process, followed by a first calcination to obtain a composite carrier;

[0015] (2) loading the composite support with a titanium source and / or a zirconium source, and then performing a second calcination to obtain a composite catalyst;

[0016] Among them, the feeding amount of the aluminum source, molecular sieve, titanium source and / or zirconium source is such that the weight ratio of aluminum oxide: molecular sieve in the composite carrier of the composite catalyst is 1: (0.1-10), and the weight ratio of the composite carrier: titanium element and / or zirconium element is 100: (1-50).

[0017] The third aspect of the present invention provides a composite catalyst prepared by the method described in the second aspect.

[0018] A fourth aspect of the present invention provides a method for preparing cyclohexenylcyclohexanone, the method comprising: subjecting cyclohexanone to a self-condensation reaction in the presence of the composite catalyst described in the first aspect or the second aspect to obtain cyclohexenylcyclohexanone.

[0019] The composite catalyst provided by the present invention has high catalytic activity in the reaction of preparing dimers (2-(1-cyclohexenyl)cyclohexanone and its resonance isomer 2-cyclohexylidenecyclohexanone) through self-condensation reaction of cyclohexanone, mild reaction conditions, high cyclohexanone conversion rate and high dimer selectivity, and high cycle stability. After the catalyst is recycled for 5 times, it can still basically maintain the activity and selectivity of the initial use. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] The first aspect of the present invention provides a composite catalyst, which comprises a composite carrier and a metal oxide supported on the composite carrier; wherein:

[0022] The composite carrier comprises alumina and molecular sieve; wherein the weight ratio of alumina to molecular sieve is 1:(0.1-10);

[0023] The metal oxide includes titanium oxide and / or zirconium oxide;

[0024] The weight ratio of the composite carrier to the metal element in the metal oxide is 100:(1-50).

[0025] The composite catalyst provided by the present invention has a specific composite carrier and a specific metal oxide as an active component, wherein the composite carrier includes alumina and molecular sieve in a specific ratio, which can increase the amount of L acid in the carrier, and also utilizes the pore structure of the molecular sieve to reduce diffusion restriction and improve selectivity; the metal oxide can effectively increase the L acid content on the catalyst surface, maintain the high thermal stability of the composite carrier, and the composite carrier and the metal oxide work together to synergistically enhance the efficiency, so that the composite catalyst has high catalytic activity in the self-condensation reaction of cyclohexanone, can take into account a high cyclohexanone conversion rate and a high dimer (2-(1-cyclohexenyl)cyclohexanone and its resonance isomer 2-cyclohexylidene cyclohexanone) selectivity, and has high cycle stability. After the composite catalyst is used for 5 times in the self-condensation reaction of cyclohexanone, the activity and selectivity at the time of initial use can still be basically maintained. In addition, the catalyst is easy to separate, can be directly filtered and recovered after the reaction, and has excellent environmental friendliness.

[0026] According to the present invention, in the composite catalyst, the composite support and the metal oxide satisfy the above-mentioned ratio, preferably, the weight ratio of the composite support to the metal element in the metal oxide is 100:(5-20). By adopting this preferred ratio of the composite support to the metal oxide, the composite catalyst can have a higher L acid content, can better maintain the high dispersibility of the active phase, and reduce the occurrence of side reactions.

[0027] According to the present invention, in the composite catalyst, for the composite carrier, the aluminum oxide and the molecular sieve therein, on the basis of satisfying the above-mentioned ratio, preferably, the weight ratio of aluminum oxide to molecular sieve is 1:(0.1-1). The use of this preferred ratio of aluminum oxide to molecular sieve can improve the strength of the carrier and make the carrier have a larger specific surface area and a multi-level pore structure, which is beneficial to improving the acidity of the composite catalyst and the dispersibility of the active components.

[0028] According to the present invention, in the composite catalyst, for the composite carrier, the molecular sieve can be selected from at least one of Hβ molecular sieve, HY molecular sieve, H-ZSM-5 molecular sieve, H-MCM-22 molecular sieve and mordenite, so that the composite carrier has a suitable multi-level pore structure and a large specific surface area, and at the same time can increase the surface acid amount of the carrier.

[0029] According to a preferred embodiment of the present invention, the molecular sieve is Hβ molecular sieve.

[0030] According to the present invention, in the composite catalyst, preferably, the metal oxide is titanium oxide and zirconium oxide, and the use of the two together can provide more L acid, improve the activity of the cyclohexanone self-condensation reaction, and increase the product yield of the reaction.

[0031] According to the present invention, when the metal oxides are titanium oxide and zirconium oxide, preferably, the weight ratio of titanium element in titanium oxide: zirconium element in zirconium oxide is 1:(0.2-5), which is more conducive to the synergistic effect of the two active components and improves the dispersibility of the active components.

[0032] According to the present invention, the composite catalyst has a relatively high L acid content. Preferably, the L acid content of the composite catalyst is 150-600 μmol / g.

[0033] In the present invention, the L acid content in the catalyst refers to the Lewis acid content, which can be determined by pyridine infrared test (Py-IR), and the calculation formula is C=1.42×I(L)×R×R / W, wherein C is the L acid content (in μmol / g), I(L) is the L acid infrared absorption peak area, R is the tablet diameter (in cm), and W is the tablet weight (in mg).

[0034] According to the present invention, preferably, the specific surface area of ​​the composite catalyst is 200-700m 2 / g.

[0035] In the present invention, the specific surface area of ​​the catalyst is measured by N2 physical adsorption-desorption and calculated using the BET formula.

[0036] According to the present invention, preferably, the average pore diameter of the composite catalyst is 1-12 nm.

[0037] In the present invention, the average pore size of the catalyst is measured by N2 physical adsorption-desorption and calculated using the BJH method.

[0038] According to a particularly preferred embodiment of the present invention, in the composite catalyst, the composite carrier comprises aluminum oxide and Hβ molecular sieve, wherein the weight ratio of aluminum oxide to Hβ molecular sieve is 1:(0.5-1); the metal oxide comprises titanium oxide and zirconium oxide, wherein the weight ratio of titanium element in titanium oxide to zirconium element in zirconium oxide is 1:(0.2-1); the weight ratio of the composite carrier to (titanium element in titanium oxide + zirconium element in zirconium oxide) is 100:(5-10); the L acid content of the composite catalyst is 300-500 μmol / g, and the specific surface area is 200-500 m 2 / g, and the average pore size is 5-9nm. The composite catalyst with this structure and parameters can further improve the cyclohexanone conversion rate and dimer ketone selectivity in the cyclohexanone self-condensation reaction, and has better cycle stability.

[0039] A second aspect of the present invention provides a method for preparing a composite catalyst, the method comprising:

[0040] (1) mixing raw materials including an aluminum source, a molecular sieve and a binder, and subjecting the resulting mixture to a molding process, followed by a first calcination to obtain a composite carrier;

[0041] (2) loading the composite support with a titanium source and / or a zirconium source, and then performing a second calcination to obtain a composite catalyst;

[0042] Among them, the feeding amount of the aluminum source, molecular sieve, titanium source and / or zirconium source is such that the weight ratio of aluminum oxide: molecular sieve in the composite carrier of the composite catalyst is 1: (0.1-10), and the weight ratio of the composite carrier: titanium element and / or zirconium element is 100: (1-50).

[0043] According to the present invention, in the preparation method of the composite catalyst, in step (1), the aluminum source is relatively broad and can be selected from conventional aluminum sources used to prepare alumina carriers. For example, the aluminum source can be selected from at least one of pseudo-boehmite, aluminum hydroxide, and aluminum sol. Preferably, the aluminum source is pseudo-boehmite.

[0044] According to the present invention, in the preparation method of the composite catalyst, in step (1), the limit of the binder is relatively wide, and the conventional binder used in preparing the catalyst carrier can be selected. For example, the binder can be selected from at least one of sesbania powder, starch, methyl cellulose and cellulose powder. Preferably, the binder is sesbania powder.

[0045] In the present invention, preferably, the weight ratio of the binder: (aluminum source + molecular sieve) is (1-5):100.

[0046] According to the present invention, in the preparation method of the composite catalyst, in step (1), the molecular sieve can be selected from at least one of Hβ molecular sieve, HY molecular sieve, H-ZSM-5 molecular sieve, H-MCM-22 molecular sieve and mordenite, so that the composite carrier has a more suitable multi-level pore structure and a large specific surface area, and the surface acid amount of the carrier can be increased. Preferably, the molecular sieve adopts Hβ molecular sieve.

[0047] In the present invention, the source of the molecular sieve is not particularly limited, and it can be prepared by a known method or a commercial product.

[0048] According to the present invention, in the preparation method of the composite catalyst, in step (1), there is no particular limitation on the mixing, as long as the raw material components can be mixed evenly to obtain a uniform mixture that meets the molding process requirements, for example, a kneading method can be used.

[0049] According to the present invention, in the preparation method of the composite catalyst, in step (1), the raw materials also include a conventional sol, such as nitric acid (concentration is 10-70% by weight). Preferably, the weight ratio of nitric acid: (aluminum source + molecular sieve) is (1-5):100.

[0050] According to the present invention, in the method for preparing the composite catalyst, in step (1), the molding process has a wide range of limitations, and molding processes and parameters known in the field of catalyst preparation can be used, preferably extrusion molding.

[0051] According to the present invention, in the preparation method of the composite catalyst, in step (1), after the molding process is completed and before the first calcination is performed, the molded product is preferably left to stand and then dried. Preferably, the drying conditions include: a temperature of 80-120°C and a time of 6-12h.

[0052] According to the present invention, in the preparation method of the composite catalyst, in step (1), the first calcination conditions include: a temperature of 400-800°C and a time of 4-16 hours. The present invention does not specifically limit the atmosphere of the first calcination, for example, the calcination can be performed in a conventional air or oxygen atmosphere.

[0053] According to the present invention, in the method for preparing the composite catalyst, in step (2), the titanium source can be selected from at least one of tetrabutyl titanate, titanium tetrachloride and titanium nitrate, and tetrabutyl titanate is preferably used.

[0054] According to the present invention, in the method for preparing the composite catalyst, in step (2), the zirconium source can be selected from at least one of zirconium oxychloride, zirconium nitrate and zirconium chloride, and zirconium nitrate is preferably used.

[0055] According to the present invention, in the preparation method of the composite catalyst, in step (2), the loading can be achieved by immersing the composite carrier in an impregnation solution containing the above-mentioned titanium source and / or zirconium source. The present invention does not particularly limit the impregnation process, and a conventional impregnation method in the art can be used, and the impregnation can be performed in one step or in multiple steps. The impregnation solution can be obtained by dissolving the titanium source and / or zirconium source in a solvent. The solvent can preferably be water.

[0056] According to the present invention, in step (2), the impregnation can be carried out at room temperature, and the impregnation time is preferably 2-12 hours.

[0057] According to the present invention, in the preparation method of the composite catalyst, in step (2), after the loading is completed and before the second calcination is performed, the loaded product is dried. Preferably, the drying conditions include: temperature of 80-120°C and time of 2-12h.

[0058] According to the present invention, in the preparation method of the composite catalyst, in step (2), the second calcination conditions include: a temperature of 450-650° C. and a time of 2-6 hours. The atmosphere of the second calcination is not particularly limited in the present invention, for example, the calcination can be carried out in a conventional air or oxygen atmosphere.

[0059] The preparation method of the composite catalyst provided by the present invention can prepare a composite catalyst having a specific composite carrier and a specific metal oxide as an active component. The composite catalyst has high catalytic activity in the self-condensation reaction of cyclohexanone, can take into account both high cyclohexanone conversion rate and high dimer selectivity, and has high cycle stability. After the composite catalyst is used for 5 times in the self-condensation reaction of cyclohexanone, it can still basically maintain the activity and selectivity of the first use. The catalyst preparation process is relatively simple, easy to separate after the reaction, can be directly filtered and recovered, and has excellent environmental friendliness.

[0060] The third aspect of the present invention provides a composite catalyst prepared by the method described in the second aspect.

[0061] In the present invention, the chemical composition, structure and performance of the composite catalyst prepared by the method described in the second aspect are the same as those of the composite catalyst described in the first aspect of the present invention, and will not be described in detail here.

[0062] A fourth aspect of the present invention provides a method for preparing cyclohexenylcyclohexanone, the method comprising: subjecting cyclohexanone to a self-condensation reaction in the presence of the composite catalyst described in the first aspect or the second aspect to obtain cyclohexenylcyclohexanone.

[0063] According to the present invention, the composite catalyst provided by the present invention is used in the method for preparing cyclohexenylcyclohexanone (2-(1-cyclohexenyl)cyclohexanone and its resonance isomer 2-cyclohexylidenecyclohexanone) provided by the present invention, so that the self-condensation reaction of cyclohexanone can be carried out under milder conditions. The method can achieve both a higher cyclohexanone conversion rate and a higher dimer selectivity. In the preparation method, the composite catalyst is recycled for 5 times after being filtered and separated, and can still basically maintain the activity and selectivity of the initial use, showing excellent cycle stability.

[0064] According to the present invention, in the method for preparing cyclohexenylcyclohexanone, preferably, the weight ratio of the composite catalyst to cyclohexanone is (2-5):100.

[0065] According to the present invention, in the method for preparing cyclohexenylcyclohexanone, preferably, the conditions of the self-condensation reaction include: temperature of 130-170° C. and time of 4-8 h.

[0066] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0067] In the following examples and comparative examples, the weight ratio of each component in the prepared positive electrode material is calculated based on the feed amount of raw materials.

[0068] Example 1

[0069] (1) 50 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0070] (2) 3.554 g of tetrabutyl titanate and 1.116 g of zirconium nitrate were dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as P1).

[0071] P1 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the metal elements in the composite carrier: metal oxide is 100:8); wherein the weight ratio of alumina:Hβ molecular sieve in the composite carrier is 1:0.5, and the weight ratio of titanium element:zirconium element in the metal oxide is 1:0.6.

[0072] The L acid content of P1 is 425 μmol / g and the specific surface area is 408 m 2 / g, and the average pore size is 8.1nm.

[0073] Example 2

[0074] (1) 70 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 5.1 g of sesbania powder was added and mixed evenly, then 3.4 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0075] (2) 2.847 g of tetrabutyl titanate and 1.488 g of zirconium nitrate were dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 hours, it was placed in an oven at 120°C and dried for 2 hours; then the dried product was placed in a muffle furnace and calcined at 550°C for 4 hours to obtain a composite catalyst (denoted as P2).

[0076] P2 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the metal elements in the composite carrier: metal oxide is 100:8); wherein the weight ratio of alumina:Hβ molecular sieve in the composite carrier is 1:0.7, and the weight ratio of titanium element:zirconium element in the metal oxide is 1:1.

[0077] The L acid content of P2 is 419 μmol / g and the specific surface area is 459 m 2 / g, and the average pore size is 9.0nm.

[0078] Example 3

[0079] (1) 100 g of HY molecular sieve and 50 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0080] (2) 1.424 g of tetrabutyl titanate and 0.744 g of zirconium nitrate were dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 hours, it was placed in an oven at 120°C and dried for 2 hours; then the dried product was placed in a muffle furnace and calcined at 550°C for 4 hours to obtain a composite catalyst (denoted as P3).

[0081] P3 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the metal elements in the composite carrier: metal oxide is 100:4); wherein the weight ratio of alumina:HY molecular sieve in the composite carrier is 1:2, and the weight ratio of titanium element:zirconium element in the metal oxide is 1:1.

[0082] The L acid content of P3 is 312 μmol / g and the specific surface area is 529 m 2 / g, and the average pore size is 7.5nm.

[0083] Example 4

[0084] (1) 100 g of H-ZSM-5 molecular sieve and 50 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt %) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0085] (2) 10.675 g of tetrabutyl titanate and 5.579 g of zirconium nitrate were dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as P4).

[0086] P4 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the metal elements in the composite carrier: metal oxide is 100:30); wherein the weight ratio of alumina:H-ZSM-5 molecular sieve in the composite carrier is 1:2, and the weight ratio of titanium element:zirconium element in the metal oxide is 1:1.

[0087] The L acid content of P4 is 467 μmol / g and the specific surface area is 298 m 2 / g, and the average pore size is 3.5nm.

[0088] Example 5

[0089] (1) 50 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0090] (2) 10.675 g of tetrabutyl titanate and 3.347 g of zirconium nitrate were dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120°C and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550°C for 4 h to obtain a composite catalyst (denoted as P5).

[0091] P5 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the metal elements in the composite carrier: metal oxide is 100:30); wherein the weight ratio of alumina:Hβ molecular sieve in the composite carrier is 1:0.5, and the weight ratio of titanium element:zirconium element in the metal oxide is 1:0.6.

[0092] The L acid content of P5 is 471 μmol / g and the specific surface area is 315 m 2 / g, and the average pore size is 7.2nm.

[0093] Example 6

[0094] (1) 100 g of Hβ molecular sieve and 50 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0095] (2) 3.554 g of tetrabutyl titanate and 1.116 g of zirconium nitrate were dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120°C and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550°C for 4 h to obtain a composite catalyst (denoted as P6).

[0096] P6 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the metal elements in the composite carrier: metal oxide is 100:8); wherein the weight ratio of alumina:Hβ molecular sieve in the composite carrier is 1:2, and the weight ratio of titanium element:zirconium element in the metal oxide is 1:0.6.

[0097] The L acid content of P6 is 402 μmol / g and the specific surface area is 512 m 2 / g, and the average pore size is 7.2nm.

[0098] Example 7

[0099] (1) 50 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0100] (2) 5.693 g of tetrabutyl titanate was dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as P7).

[0101] P7 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the composite carrier: titanium element in the metal oxide is 100:8); wherein the weight ratio of alumina:Hβ molecular sieve in the composite carrier is 1:0.5.

[0102] The L acid content of P7 is 438 μmol / g and the specific surface area is 414 m 2 / g, and the average pore size is 7.8nm.

[0103] Comparative Example 1

[0104] (1) 50 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0105] (2) 42.700 g of tetrabutyl titanate was dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as DP1).

[0106] DP1 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the composite carrier: the titanium element in the metal oxide is 100:60); wherein the weight ratio of alumina: Hβ molecular sieve in the composite carrier is 1:0.5.

[0107] The L acid content of DP1 is 687 μmol / g and the specific surface area is 283 m 2 / g, and the average pore size is 5.9nm.

[0108] Comparative Example 2

[0109] (1) 100 g of pseudo-boehmite was mixed, 3 g of sesbania powder was added and the mixture was mixed evenly, then 2 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then dried in an oven at 80° C. for 6 h; and the dried product was calcined in a muffle furnace at 600° C. for 4 h to obtain an alumina carrier;

[0110] (2) 5.693 g of tetrabutyl titanate was dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned alumina carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as DP2).

[0111] DP2 has an alumina support and a metal oxide supported on the alumina support (the weight ratio of the alumina support: the titanium element in the metal oxide is 100:8).

[0112] The L acid content of DP2 is 362 μmol / g and the specific surface area is 187 m 2 / g, and the average pore size is 5.9nm.

[0113] Comparative Example 3

[0114] (1) 5 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 3.15 g of sesbania powder was added and mixed evenly, then 2.1 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0115] (2) 5.693 g of tetrabutyl titanate was dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as DP3).

[0116] DP3 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the composite carrier: titanium element in the metal oxide is 100:8); wherein the weight ratio of alumina: Hβ molecular sieve in the composite carrier is 1:0.05.

[0117] The L acid content of DP3 is 371 μmol / g and the specific surface area is 193 m 2 / g, and the average pore size is 6.0nm.

[0118] Comparative Example 4

[0119] (1) 50 g of Hβ molecular sieve and 100 g of pseudo-boehmite were mixed, 4.5 g of sesbania powder was added and mixed evenly, then 3 g of nitric acid (concentration of 66.5 wt%) was added dropwise and kneaded for 30 min, and the resulting mixture was extruded into strips; the extruded strips were allowed to stand at 25° C. for 3 h, and then placed in an oven at 80° C. for 6 h; and then the dried product was placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a composite carrier;

[0120] (2) 1.472 g of ammonium molybdate was dissolved in 20 g of deionized water to obtain an impregnation solution, and the impregnation solution was poured into 10 g of the above-mentioned composite carrier and shaken evenly. After standing for 2 h, it was placed in an oven at 120° C. and dried for 2 h; then the dried product was placed in a muffle furnace and calcined at 550° C. for 4 h to obtain a composite catalyst (denoted as DP4).

[0121] DP4 has a composite carrier and a metal oxide loaded on the composite carrier (the weight ratio of the composite carrier: molybdenum element in the metal oxide is 100:8); wherein the weight ratio of alumina:Hβ molecular sieve in the composite carrier is 1:0.5.

[0122] The L acid content of DP4 is 198 μmol / g and the specific surface area is 406 m 2 / g, and the average pore size is 7.8nm.

[0123] Comparative Example 5

[0124] The composite support prepared in step (1) of Example 7 was used as a catalyst product (denoted as DP5).

[0125] Test Case

[0126] 1. Catalyst activity evaluation test

[0127] The catalysts P1-P7 and DP1-DP5 prepared in the above Examples 1-7 and Comparative Examples 1-5 were used to carry out a cyclohexanone self-condensation reaction, wherein the weight ratio of the catalyst to the cyclohexanone was 5:100, the reaction temperature was 150° C., and the reaction time was 4 h. The products after the reaction were analyzed by offline chromatography, and the results are shown in Table 1.

[0128] Table 1

[0129]

[0130]

[0131] As can be seen from Table 1, the composite catalyst provided by the present invention requires mild reaction conditions and can bring about a higher cyclohexanone conversion rate and a higher dimer selectivity in the cyclohexanone self-condensation reaction. Under the above test conditions, a cyclohexanone conversion rate ≥ 80% and a dimer selectivity ≥ 90% can be achieved.

[0132] 2. Catalyst cyclic stability test

[0133] The above catalysts P1, P5 and DP1-DP5 were used to carry out the self-condensation reaction of cyclohexanone, wherein the weight ratio of catalyst to cyclohexanone was 5:100, the reaction temperature was 150°C, and the reaction time was 4h. After the reaction, the catalyst was washed with ethanol 3 times, then dried at 120°C for 4h and calcined at 500°C for 4h, and the calcined catalyst was used again for the above self-condensation reaction of cyclohexanone, and this cycle was repeated 5 times. The results are shown in Table 2.

[0134] Table 2

[0135]

[0136] As can be seen from Table 2, the composite catalyst provided by the present invention has high cyclic stability. After the catalyst is recycled for 5 times under the above test conditions, it can basically maintain the activity and selectivity of the initial use.

[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite catalyst, characterized in that: The composite catalyst comprises a composite carrier and a metal oxide supported on the composite carrier; wherein the composite carrier comprises alumina and molecular sieve; wherein the weight ratio of alumina to molecular sieve is 1:(0.1-10); The metal oxide includes titanium oxide and / or zirconium oxide; The weight ratio of the composite carrier to the metal element in the metal oxide is 100:(1-50).

2. The composite catalyst according to claim 1, wherein The weight ratio of the composite carrier to the metal element in the metal oxide is 100:(5-20).

3. The composite catalyst according to claim 1 or 2, wherein The weight ratio of alumina: molecular sieve is 1:(0.1-1); Preferably, the molecular sieve is at least one selected from Hβ molecular sieve, HY molecular sieve, H-ZSM-5 molecular sieve, H-MCM-22 molecular sieve and mordenite, and more preferably Hβ molecular sieve.

4. The composite catalyst according to any one of claims 1 to 3, wherein The metal oxides are titanium oxide and zirconium oxide; Preferably, the weight ratio of titanium element in titanium oxide to zirconium element in zirconium oxide is 1:(0.2-5).

5. The composite catalyst according to any one of claims 1 to 4, wherein The L acid amount of the composite catalyst is 150-600 μmol / g; And / or, the specific surface area of ​​the composite catalyst is 200-700m 2 / g; And / or, the average pore size of the composite catalyst is 1-12 nm.

6. A method for preparing a composite catalyst, characterized in that: The method comprises: (1) mixing raw materials including an aluminum source, a molecular sieve and a binder, and subjecting the resulting mixture to a molding process, followed by a first calcination to obtain a composite carrier; (2) loading the composite support with a titanium source and / or a zirconium source, and then performing a second calcination to obtain a composite catalyst; Among them, the feeding amount of the aluminum source, molecular sieve, titanium source and / or zirconium source is such that the weight ratio of aluminum oxide: molecular sieve in the composite carrier of the composite catalyst is 1: (0.1-10), and the weight ratio of the composite carrier: titanium element and / or zirconium element is 100: (1-50).

7. The preparation method according to claim 6, wherein: The aluminum source is selected from at least one of pseudo-boehmite, aluminum hydroxide and aluminum sol, preferably pseudo-boehmite; and / or, the titanium source is selected from at least one of tetrabutyl titanate, titanium tetrachloride and titanium nitrate, preferably tetrabutyl titanate; and / or, the zirconium source is selected from at least one of zirconium oxychloride, zirconium nitrate and zirconium chloride, preferably zirconium nitrate; And / or, the molecular sieve is at least one selected from Hβ molecular sieve, HY molecular sieve, H-ZSM-5 molecular sieve, H-MCM-22 molecular sieve and mordenite, preferably Hβ molecular sieve; And / or, the first calcination conditions include: temperature of 400-800° C., time of 4-16 h; And / or, the second calcination conditions include: temperature of 450-650° C. and time of 2-6 hours.

8. The composite catalyst obtained by the preparation method according to claim 6 or 7.

9. A method for preparing cyclohexenylcyclohexanone, characterized in that: The method comprises: subjecting cyclohexanone to a self-condensation reaction in the presence of the composite catalyst described in any one of claims 1 to 5 and 8 to obtain cyclohexenylcyclohexanone.

10. The method according to claim 9, wherein: The weight ratio of the composite catalyst to cyclohexanone is (2-5):100; And / or, the conditions of the self-condensation reaction include: temperature of 130-170° C. and time of 4-8 h.

Citation Information

Patent Citations

  • Method for producing cyclohexenyl anone from continuous condensating anone

    CN101003471A

  • Process for producing 2-(cyclohex-1'-enyl)cyclohexanone

    CN102557908A

Cited By

  • Ethylene oxychlorination catalyst and preparation method thereof, and method for preparing 1, 2-dichloroethane through ethylene oxychlorination

    CN120421025A